SMK MUHAMMADIYAH BANDA ACEH STUDENTS' PERCEPTION ON THE TOEIC COMPETENCY TEST - Sarair; Lina Farsia (University of Muhammadiyah Malang, 2023)
The purpose of this study is to describe how students at SMK Muhammadiyah Banda Aceh feel about the TOEIC competency test and pinpoint any obstacles they may have encountered while taking the test. Using the purposive sampling technique, 30 children from class 2 at SMK Muhammadiyah Banda Aceh were chosen as the sample for this study. Two questionnaires were used to gather data. The analysis findings suggest that most students have a favorable opinion on the TOEIC test. They believed that taking the test helped them improve their English, and they would suggest it to others. However, they also struggle to read test texts, comprehend challenging terms and settings, and respond to questions. Additionally, some students lacked confidence and were unfamiliar with the test question styles. This study found that the TOEIC test has a good effect, but also highlights the difficulties that students experience. The recommendations include improving students' comprehension of exam instructions, addressing issues by understanding challenging terms and circumstances, and offering assistance to increase students' confidence. The TOEIC test and more efficient methods of English language instruction were predicted to benefit from the findings of this study.